Javanese Islamic Mysticism in the Perspective of Serat Wirid Idayat Jati - Ramdan Hakim, Arif; Radea Yulli Hambali; Ahmad Gibson al bustomi (al-Afkar, Journal For Islamic Studies, 2024)
Javanese Islamic mysticism is a unique branch of Islamic mysticism, which reflects a harmonious combination of Islamic teachings and Javanese culture. One of the Javanese literary works which is an important source in understanding Javanese Islamic mysticism is Serat Wirid Hidayat Jati. This fiber includes mystical teachings, religious practices, and world views that characterize the uniqueness of Javanese spirituality which is very close to Islamic teachings. Therefore, this research aims to explore and analyze Javanese Islamic Mysticism in Serat Wirid Hidayat Jati with a focus on worldview, religious practices, and the influence of Javanese culture in the perspective of the fiber. This research aims to understand the concept of Javanese Islamic Mysticism in Serat Wirid Hidayat Jati, analyze religious practices in it, and identify the influence of Javanese culture in its delivery. This research uses a qualitative approach by analyzing the text of Serat Wirid Hidayat Jati and involving related literature studies. The data obtained from the text will be analyzed in depth to reveal concepts, practices and cultural influences in Javanese Islamic mysticism. The results of this research will reveal the concept of Javanese Islamic Mysticism in Serat Wirid Hidayat Jati, including the worldview, religious practices, and Javanese cultural influences contained in the text. This research is expected to provide a deeper understanding of Javanese Islamic Mysticism from the perspective of Serat Wirid Hidayat Jati. This can provide richer insight into the relationship between religion and culture in the Javanese context, as well as the contribution of literary works such as Serat Wirid Hidayat Jati in understanding Islamic mysticism in Indonesia.